Measurement and analysis of atmospheric optical turbulence in Lhasa based on thermosonde. (May 2020) - Wu, Su; Hu, Xiaodan; Han, Yajuan; Wu, Xiaoqing; Su, Changdong; Luo, Tao; Li, Xuebin
Abstract: In this paper, we have analyzed the wind, temperature and optical turbulence index structure constant ( C n 2 ) that are directly measured for the first time at Lhasa, Tibet. Unlike other mid-or-low latitude regions, the wind speed in Lhasa increases with the altitude according to the wind profiles, besides a strong wind speed near the tropopause. The temperature profiles indicate a large temperature change near the tropopause. The optical turbulence profiles show daily variation. When the altitude is below 12 km, except for individual points, the C n 2 values during morning and evening are basically in the same range of 10 −17 -10 −15  m -2/3 . When altitude is above 12 km, the intensity of turbulence during the morning in Lhasa is 1–2 orders of magnitude larger than that of the evening. In addition, we propose a turbulence profile model on the basis of Hufnagel-valley model to calculate the integrated values of the refractive index structure constants of the entire atmosphere, such as the Fried parameter, the seeing, the coherence time and the isoplanatic angle. The mean atmospheric coherence length r0 is 5.77 cm. Differences in these parameters between morning and evening also illustrate the stronger turbulence in the morning than evening. Highlights: Wind, temperature, optical turbulence index structure constant ( C n 2 ) are directly measured for the first time at Lhasa Tibet. The integrated values of the refractive index structural constants for the entire atmosphere are calculated and analyzed. The relation between turbulence and wind speed as well as that between turbulence and temperature in Lhasa is analyzed. Turbulence profile model based on Hufnagel-valley model for Tibet is proposed in the paper to evaluate the turbulence.